2019
DOI: 10.1088/1361-6579/ab2af6
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral assessment of body core temperature through axillar, tympanic and inner canthi thermometers in a young population

Abstract: There are several sites in which the human body core temperature can be estimated and used to identify febrile states in a threat of pandemic situations at high-populational-traffic places (e.g. airports, ports, universities, schools, public buildings). In these locations, a fast method is required for temperature screening of masses. The most common methods are axillar and tympanic thermometers. However, in addition, measurement of the inner canthi (IC) of the eye with infrared thermal (IRT) imaging has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
0
14
0
3
Order By: Relevance
“…To minimize the measurement error, distances between 80 and 120 cm and angles as close as possible to 90 • should be used when the inner-canthi of the eye temperature is recorded with conventional lenses and standard image analysis software for fever screening [43]. Vardasca et al [44] also demonstrated, employing the Bland-Altmann limits of agreement, that the bilateral difference of the inner canthus of the eyes is negligible.…”
Section: Inner Canthi Identification and Face Segmentation Algorithmsmentioning
confidence: 99%
“…To minimize the measurement error, distances between 80 and 120 cm and angles as close as possible to 90 • should be used when the inner-canthi of the eye temperature is recorded with conventional lenses and standard image analysis software for fever screening [43]. Vardasca et al [44] also demonstrated, employing the Bland-Altmann limits of agreement, that the bilateral difference of the inner canthus of the eyes is negligible.…”
Section: Inner Canthi Identification and Face Segmentation Algorithmsmentioning
confidence: 99%
“…The temperature of venous blood and afferent signals from thermo-sensitive nerves on the body surface are used by the brain as reference temperatures for regulating autonomic and behavioral responses around a Tb set-point [8]. As the measurement of venous blood temperature is invasive and impractical to perform in research and clinical settings, the most common sites for indirect measurement of Tc are the rectum, esophagus, and gastrointestinal tract [68][69][70][71] for research, and the axillar, sub-lingual, ear canal, and forehead for diagnosis of fever [7]. In this review, and unless specified, Tc is used generically to encompass temperatures measured in the sites used for research [1,7,72,73].…”
Section: Core Temperaturementioning
confidence: 99%
“…A base da comparação foi avaliar as diferenças de temperatura bilateral, uma vez que os humanos são simétricos termicamente. Com base nos achados desta pesquisa, apesar de todos os métodos terem sido capazes de estimar a temperatura central do corpo, sugere-se o uso de imagens de termografia no canto medial do olho, uma vez que é um procedimento rápido, confiável e reproduzível para triagem em massa [27].…”
Section: Arritmiasunclassified
“…A termografia oferece um excelente meio para determinar qualitativamente a temperatura do BTT, mas há muitas dificuldades em obter uma medição absoluta, como: exigir um ambiente controlado, limitar a interferência do infravermelho, posicionamento e inicialização da câmera térmica, falta de treinamento dos operadores, presença de artefatos (como máscaras, óculos, chapéus, cachecóis), presença de uma referência de temperatura, diferentes formatos de arquivos pelos fabricantes e total desconhecimento dos padrões existentes nos locais de triagem. Tudo isso pode ser tratado, mas exige tempo, conscientização e treinamento [27]. Desde a pandemia da SARS em 2003, quando se iniciou o emprego da técnica no rastreamento de pessoas, cientistas e entidades de metrologia elaboraram diretrizes de padronização para garantir o melhor desempenho para esta finalidade.…”
Section: Arritmiasunclassified